Adolescent Sleep Problems and Susceptibility to Peer Influence. Issue 2 (March 2022) - Semenza, Daniel C.; Jackson, Dylan B.; Testa, Alexander; Meldrum, Ryan C.
Susceptibility to peer influence among adolescents is associated with a variety of negative interpersonal and psychosocial outcomes. Although proper sleep is crucial for adolescent development and well-being, no study to date has examined the influence of sleep problems on susceptibility to peer influence. We assess this relationship using two waves of data ( n  = 907; 50% male, 18% non-White) from the Study of Early Child Care and Youth Development (SECCYD). Results of a series of multivariate regression models demonstrate that sleep problems are positively associated with susceptibility to peer influence, net of pertinent demographic characteristics, theoretical controls, and prior susceptibility to peer influence. These findings suggest that efforts to improve sleep quality and quantity among adolescents, including educational sleep hygiene programs and later school start times, may serve to curtail susceptibility to peer influence and improve various aspects of wellbeing.